Epidemiology of African swine fever in Africa today : Sylvatic cycle versus socio‐economic imperatives - (:unkn) unknown (My University, 2019)
African swine fever (ASF) is believed to have evolved in eastern and southern Africa in a sylvatic cycle between common warthogs (Phacochoerus africanus) and argasid ticks of the Ornithodoros moubata complex that live in their burrows. The involvement of warthogs and possibly other wild suids in the maintenance of ASF virus means that the infection cannot be eradicated from Africa, but only prevented and controlled in domestic pig populations. Historically, outbreaks of ASF in domestic pigs in Africa were almost invariably linked to the presence of warthogs, but subsequent investigations of the disease in pigs revealed the presence of another cycle involving domestic pigs and ticks, with a third cycle becoming apparent when the disease expanded into West Africa where the sylvatic cycle is not present. The increase in ASF outbreaks that has accompanied the exponential growth of the African pig population over the last three decades has heralded a shift in the epidemiology of ASF in Africa, and the growing importance of the pig husbandry and trade in the maintenance and spread of ASF. This review, which focuses on the ASF situation between 1989 and 2017, suggests a minor role for wild suids compared with the domestic cycle, driven by socio‐economic factors that determine the ability of producers to implement the control measures needed for better management of ASF in Africa.
Keywords: African Research